Molecular Investigations into the Catalytic Mechanisms and Inhibition of the Aminoglycoside Antibiotic Resistance Enzymes APH(3')-Illa and AAC(6')-APH(2") - Boehr, Douglas David (My University, 2003)
The golden age of antibiotics may be at an end. These compounds found clinical use in the 1940s, and their medical benefits were readily apparent, curing once fatal diseases and increasing life expectancy. However, bacteria have responded successfully to this threat by developing resistance to a multitude of antibiotics, and now, once treatable pathogens are again on the warpath. One of the classes of antibiotics to which resistance has arisen is the aminoglycoside aminocyclitols that specifically target the prokaryotic ribosome. The most clinically relevant form of aminoglycoside resistance is the expression of modifying enzymes, including APH(3')-IIIa and AAC(6')-APH(2") that catalyze the phosphorylation and/or acetylation of a wide range of aminoglycosides. Application of potent, specific inhibitors to these enzymes can provide a means of overcoming resistance, and a thorough understanding of these enzymes will aid in this endeavor. Towards this end, the molecular mechanisms of catalysis for aminoglycoside phosphorylation and acetylation have been investigated. Enzyme-catalyzed aminoglycoside phosphorylation likely operates through a dissociative-like mechanism where bond breakage predominates in the transition-state, similar to what is observed in the structurally similar serine/threonine protein kinase family, whereas aminoglycoside acetylation catalyzed by AAC(6')-APH(2") utilizes an active site base. Through these studies, a number of inhibitors have also been identified including wortmannin that specifically labels a highly conserved lysine In AAC(6')-APH(2"), 1-bromomethylphenanthrene that covalently modifies the acetyltransferase aspartate base in AAC(6')-APH(2"), and indolocidin, a peptide that inhibits a broad range of aminoglycoside resistance enzymes. The studies and molecules presented here will serve as the basis for the development of future inhibitors of these enzymes and the eventual triumph over aminoglycoside antibiotic resistance.
Keywords: Biochemistry; Biochemistry